H. elongata aminotransferase: a resourceful enzyme for modern biocatalysis - Planchestainer, Matteo (2018)
The standard preparation of valuable chemical compounds often exploits reactions that are plagued by suboptimal yields and a considerable amount of toxic waste, especially when it comes to asymmetric synthesis and metal catalysts. In the quest to achieve cleaner processes, enzymes are compelling alternatives; these natural devices offer "green" and efficient reactions. Furthermore, they are generally very enantioselective yielding optically pure products. Enzymes however have also many drawbacks: they especially suffer when forced to work under non-physiological conditions. A solution could be to exploit extremophile organisms, which are naturally adapted to work in “extreme” environments, as sources of new biocatalysts. Among the various classes of enzymes, aminotransferases (EC 2.6.1) are particularly interesting, since these biocatalysts are able to catalyze the amino transfer between two molecules, a reaction particularly difficult to perform with traditional synthetic approaches. An aminotransferase from Halomonas elongata (HEWT), a halotolerant organism, was isolated and characterized to verify its ability to work in the presence of organic solvents. Despite a broad substrate scope, HEWT was poorly active against ketones under standard condition. The investigation of the stereoelectronic effects of the reactions through a series of rationally engineered variants, led to a better understanding of the residues in the active pocket but produced only minimal improvement in activity. HEWT was therfore evolved towards the desired substrates applying iterative cycles of mutagenesis and screening to select the ameliorated protein. The development of an efficient high-throughput screening allowed isolation novel mutants with enhanced activity towards substituted acetophenones and small aliphatic ketones, with up to 60-fold improvement in the enzyme reactivity against para-CN-acetophenone. Furthermore, HEWT stability and tolerance were improved through protein immobilization, which showed excellent results especially in the presence of solvents. The methodology adopted was further developed by installing a protein spacer to preserve the integrity of the enzyme and prevent the significant loss of activity upon non-specific covalent linking. Immobilised HEWT was then applied in continuous flow biotransformations for the efficient production and isolation of amines. This cutting-edge approach showed about one order of magnitude higher synthetic efficiency with respect to batch processes and opened new avenues for the efficient application of enzymes in biotechnology.